Structurally heterogeneous ribosomes cooperate in protein synthesis in bacterial cells - Helena-Bueno, Karla; Kopetschke, Sophie; Filbeck, Sebastian; Chan, Lewis I.; Birsan, Sonia; Baslé, Arnaud; Hudson, Maisie; Pfeffer, Stefan; Hill, Chris H.; Melnikov, Sergey V. (Nature Communications, 2025)
Ribosome heterogeneity is a paradigm in biology, pertaining to the existence of structurally distinct populations of ribosomes within a single organism or cell. This concept suggests that structurally distinct pools of ribosomes have different functional properties and may be used to translate specific mRNAs. However, it is unknown to what extent structural heterogeneity reflects genuine functional specialization rather than stochastic variations in ribosome assembly. Here, we address this question by combining cryo-electron microscopy and tomography to observe individual structurally heterogeneous ribosomes in bacterial cells. We show that 70% of ribosomes in Psychrobacter urativorans contain a second copy of the ribosomal protein bS20 at a previously unknown binding site on the large ribosomal subunit. We then determine that this second bS20 copy appears to be functionally neutral. This demonstrates that ribosome heterogeneity does not necessarily lead to functional specialization, even when it involves significant variations such as the presence or absence of a ribosomal protein. Instead, we show that heterogeneous ribosomes can cooperate in general protein synthesis rather than specialize in translating discrete populations of mRNA.